Teacher’s Strategy in Overcoming Learning Loss of Online Learning at the 3T Area of Lampung - Muhassin, Mohammad; Reftyawati, Dian; Nawawi, M.; Hidayati, Dewi Ayu (Universitas Islam Negeri Raden Intan Lampung, 2026)
Education encountered substantial challenges due to changes in the learning system caused by the COVID-19 pandemic, one of which is learning loss due to online learning. This study aims to investigate teachers' strategies in overcoming learning loss of online learning in the 3T area of Lampung. This is a kind of qualitative descriptive research using a case study approach in MA Nurul Iman Sekincau, West Lampung, as one of the 3T areas. The results of the study found that the change in the education system through online learning has caused learning loss in students at MA Nurul Iman Sekincau. Learning loss refers to the decline in knowledge and enthusiasm for learning in students, rendering learning ineffective. In online learning, there are various obstacles faced, such as students who do not have quotas, are constrained by signals, are constrained in accessing applications, and there are even students who do not have gadgets. Thus, the right strategy is needed for teachers to overcome learning problems during the pandemic. The study contributes to educational management by emphasizing contextual, resource-based strategies in disadvantaged regions.